Application of Oxidative Coupling Reactions for Estimation of Lercanidipine Hydrochloride in Formulations - MANIKYA SASTRY*, T.; RAMAKRISHNA†, K. (Asian Journal of Chemistry, 2024)
Two simple and sensitive visible spectrophotometic methods (A and B) have been developed for the assay of lercanidipine hydrochloride in bulk and formulations. Methods A and B are based on the formation of colour species by means of forming oxidative coupling reactions with 4-aminophenazone/IO4 (λmax = 520) and N,N′-dimethylamino-p-phenyl-enediamine/chloramine- T (λmax = 550). The results of analysis have been validated statistically and recovery studies range from 99.4 to 100.5 % for the routine assay of lercanidipine hydrochloride formulations.